Managing two cases of twin anemia–polycythemia sequence in monochorionic twin pregnancies - Zhang, Yongke; Liang, Yiheng; Chen, Ran; Zhang, Dirong; Wu, Jing (Frontiers in Medicine, 2025)
Background Twin anemia–polycythemia sequence (TAPS) is a rare monochorionic complication. In this study, we discuss the management of two cases of TAPS with different conditions. Case presentation Patient 1 was a 34-year-old multigravida in whom the fetal middle cerebral artery peak systolic velocities (MCA-PSVs) were 0.86 multiples of the median (MoM) and 2.0 MoM at 33 weeks of gestation. After cesarean section, stage 3 TAPS was confirmed according to the ultrasound findings and hemoglobin results of the newborns and placenta examination after birth. Patient 2 was a nulligravida who was diagnosed with stage 2 TAPS at 18 weeks of gestation. The patient underwent fetoscopic laser surgery. Ultrasonography monitoring of the MCA-PSVs was performed on a schedule after surgery, with a good status but selective intrauterine growth restriction of one cotwin. The newborns reached their normal development milestones after spontaneous preterm birth. Conclusion Optimal management should be carefully selected for patients with different TAPS conditions.